Transformational Leadership in Modern Government in Indonesia - Dea Melati; Ganden Syariep Saputra; Muhammad Afdhal Abdiansyah (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
This study examines the role of transformational leadership in strengthening modern governance and encouraging innovation in public services. The urgency of this study arises from the challenges of contemporary bureaucracy, ranging from the need for bureaucratic reform, service digitalization, to increasing accountability and public trust, which demand a leadership model that can inspire, motivate, and encourage innovation. The objectives of this study are (1) to reconstruct the concept and dimensions of transformational leadership in the context of government; (2) to examine empirical evidence of the application of this leadership style to service innovation and bureaucratic performance; and (3) to formulate policy recommendations for strengthening public leadership capacity. The method used is a literature study (library research) with a qualitative descriptive-analytical approach: searching for journal articles, academic books, and selected policy documents, thematic classification, and analytical synthesis of the four dimensions of transformational leadership. The results of the study indicate that transformational leadership through idealized influence, inspirational motivation, intellectual stimulation, and individual attention has the potential to increase service innovation, apparatus commitment, and public accountability when supported by managerial capacity and a supportive organizational climate. This article recommends (a) a training and coaching-based transformational leadership development program for public officials; (b) strengthening dynamic managerial capacity at the middle level to accelerate innovation; and (c) a further research agenda that examines implementation mechanisms in various regional contexts.